Synthesis, Characterization, Docking Studies and in vitro Response of New Camptothecin Derivatives towards Oral Squamous Cell Carcinoma - Ugrappa, S.; Jagadeesan, D.; Lalitha, P.; Ravichandran, M.; Solyappan, M.; Khor, G.H.; Wu, Y.S.; Balakrishnan, V.; Thangeswaran, D.; Fuloria, S. (Asian Journal of Chemistry, 2024)
Evidence suggests heterocyclic rings as the essential component of various available chemotherapeutics. Present study was aimed to carry out the molecular docking, synthesis, characterization and response of new camptothecin derivatives (NCDs) towards OSCC cell lines. To achieve the aim of the study, new camptothecin derivatives were designed to perform molecular docking against the target protein Human DNA Topoisomerase-1 (1T8I). Molecules 2 and 3 with high docking scores were subjected to synthesis. In current investigation, NCDs were synthesized by cyclization of imino analogue (2) into a new azetidinone derivative (3) on treatment with triethylamine and chloroacetyl chloride. Synthesized NCDs were characterized using IR, NMR and mass analysis. The NCDs were further subjected to antiproliferation study using CAL-27 (OSCC), followed by in vitro DNA relaxation assay and cell cycle analysis. The results of the docking of CPT-11 against Human DNA Topoisomerase-1 Duplex (PDB ID: 1T8I) in present study revealed compound 2 and 3 exhibited high docking score among all camptothecin analogues. Present study successfully synthesized and elucidated the structures of NCD 2 and 3. The antiproliferation study results revealed that NCD 2 and NCD 3 offered an IC50 of 34.73 µg/mL and 62.5 µg/mL, respectively. The DNA relaxation assay exhibited the inhibition action of synthesized NCDs (IC50 concentration) against topoisomerase enzyme. Moreover, the cell cycle analysis revealed that both NCDs arrested cancer cells in ‘S’ phase. Though the present study highlights the potential of NCDs against oral squamous cell carcinoma, however, the present study also recommends that the synthesized NCDs must be further evaluated for preclinical and clinical significance.